2016
DOI: 10.1051/meca/2015113
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of self-loosening of a bolted assembly under transversal load

Abstract: Self-loosening of bolts is a problem encountered in many industrial fields, and especially in aviation. The purpose of this paper is to study the self-loosening phenomenon numerically through an assembly consisting of two plates assembled by a bolt and subjected to a transversal dynamic load. First, a 3D finite element model is developed, with contact elements and all geometrical details, including the real thread geometry with its helix angle. This leads to many degrees of freedom and long calculation time. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Zhou [2] studied the effect of load amplitude and material under shear load, and the results showed that the amplitude of shear load at a critical point below which the bolt will not be completely loose. Ksentini [3] studied the related values of bolt assembly loosening under the transverse load. Jiang [4] analyzed the loosening performance of bolts in the connection structure of super-elastic shape memory alloy material.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou [2] studied the effect of load amplitude and material under shear load, and the results showed that the amplitude of shear load at a critical point below which the bolt will not be completely loose. Ksentini [3] studied the related values of bolt assembly loosening under the transverse load. Jiang [4] analyzed the loosening performance of bolts in the connection structure of super-elastic shape memory alloy material.…”
Section: Introductionmentioning
confidence: 99%
“…Gong et al [22] analyzed local slippage accumulation on the bearing surface using the modified Iwan's model and developed a thorough understanding of the loosening mechanism. Various theoretical models [23][24][25][26][27][28][29][30][31][32][33] have been proposed to understand the mechanism of loosening caused by complete slippage under transversal vibration. Yokoyama et al [34] investigated the loosening of bolted joints subjected to cyclic torqueing.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the aforementioned theoretical and experimental research efforts, many scholars have also analyzed the load transfer mechanism of the anchoring system through numerical simulation. [17][18][19] These include analysis of the force balance and the shear stress distribution in each section of the anchor associated with the group anchor system, 20 3D numerical simulation of the rock with soft-hard combination, and the pressuredispersed anchor cable. [21][22][23] The results show that the axial force and the shear stress distributions on the anchorage interface are closely related to the rock properties, bolt material, geometric parameters, and thickness of the bonding layer.…”
Section: Introductionmentioning
confidence: 99%